2016
DOI: 10.1007/jhep10(2016)139
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive and non-diffractive wounded nucleons and final states in pA collisions

Abstract: Abstract:We review the state-of-the-art of Glauber-inspired models for estimating the distribution of the number of participating nucleons in pA and AA collisions. We argue that there is room for improvement in these model when it comes to the treatment of diffractive excitation processes, and present a new simple Glauber-like model where these processes are better taken into account. We also suggest a new way of using the number of participating, or wounded, nucleons to extrapolate event characteristics from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 76 publications
0
68
0
Order By: Relevance
“…As discussed in ref. [9], taking averages over target nucleon states is enough for calculations of cross sections and the number of wounded nucleons in pA collisions, provided diffractively excited nucleons are also counted as wounded nucleons. For a generalisation to AA collisions it is, however, necessary to take into account individual fluctuations in both projectile and target nucleons.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in ref. [9], taking averages over target nucleon states is enough for calculations of cross sections and the number of wounded nucleons in pA collisions, provided diffractively excited nucleons are also counted as wounded nucleons. For a generalisation to AA collisions it is, however, necessary to take into account individual fluctuations in both projectile and target nucleons.…”
Section: Introductionmentioning
confidence: 99%
“…This cross section was dubbed the "wounded cross section" in ref. [35], and can be constructed by generalizing the inelastic cross section, using eq. (7.4).…”
Section: Results III -Dynamic Colour Fluctuations In Glauber Calculatmentioning
confidence: 99%
“…In ref. [35] is was found that a log-normal distribution (see eq. (B.2) in appendix B) describes fluctuations generated by a dipole approach better.…”
Section: Results III -Dynamic Colour Fluctuations In Glauber Calculatmentioning
confidence: 99%
See 2 more Smart Citations